PELATIHAN LITERASI DIGITAL UNTUK GURU SEKOLAH KHUSUS DALAM MEMBUAT BUKU INTERAKTIF BERBASIS AUGMENTED REALITY - Ramdhan, Syaipul; Maisaroh, Siti; Fitri, Shafirah (Jurnal Abdi Insani, 2024)
Children in special needs schools have visual, hearing, physical, intellectual and social disabilities. The current problem in SKh Caraka Pratama related to teaching activities carried out by teachers is using textbooks that contain too much narrative information. At the same time, students only absorb very little information. The purpose of this activity is to provide training in skills to create interactive books based on Augmented Reality. The method used in organizing this training is through three stages, including: the identification stage with surveys and problem mapping, the empowerment stage with the provision of tools and assistance, and the evaluation stage with activity achievements and questionnaires. The results of this training are that teachers create interactive printed books and Augmented Reality applications that can later be used as a fun teaching tool, the initial teacher competency test (pre-test) got a score of 60, while after the training the score increased to 95.